Evaluasi Layanan Referensi di Perpustakaan Universitas Andalas - Nilam, Putri; Primadesi, Yona (Departemen Informasi Perpustakaan dan Kearasipan, 2024)
This research aims to determine deficiencies or gaps that occur in the Andalas University Library reference services, so that improvements can be made according to targets. This research uses the DEM (Discrepancy Evaluation Model) model or what is called the gap evaluation model which focuses on three stages, namely input, process and output. This approach uses quantitative research with descriptive methods. Data collection techniques through questionnaires and interviews. This research data was obtained from distributing questionnaires to readers who used reference services. The population in this study were 264 users of Andalas University library reference services from January 2022 to August 2022. The samples in this study were taken using a non-probability sampling design with the Accidental Sampling technique so that a sample of 73 people was obtained. The results of research regarding the evaluation of reference services at the Andalas University Library are described as follows: First, the Librarian dimension obtained an average of 2.70. Second, the Collection dimension which obtained an average of 2.39. Third, the catalog dimension obtained an average of 2.85. Fourth, the Library Reference Service dimension which obtained an average of 2.47. Fifth, the Information Retrieval Service dimension which obtained an average of 2.87. Sixth, the Visitor Data dimension obtained an average of 2.94. Seventh, the Collection dimension obtained an average of 2.93. Based on the results of this research, it can be concluded that the evaluation of reference services at the Andalas University Library obtained an overall average score of 2.73. This score is in the good interval class, namely 2.50-3.24, which means that reference services have been implemented well at the Andalas University Library.